Investigating the Impact of Peer Assessment on Enhancing EFL Writing Skills The Case of Second-Year Bachelor Students of English at the University of Souk-Ahras - Roguia SENANI (My University, 2023)
This study aims to investigate the effectiveness of peer assessment in enhancing the writing abilities of second-year English Language bachelor students at Mohamed Cherif Messaadia University in Souk-Ahras. The primary hypothesis, which suggests that the utilization of peer assessment can improve students' writing skills, was tested using a questionnaire administered to students and interviews with teachers. The data collected indicated that peer assessment positively influences the development of learners' writing skills. This is because peer assessment enables students to identify their strengths and weaknesses, obtain feedback from their peers, and learn from their mistakes. By simplifying the writing task and fostering a heightened awareness of the value of feedback on their writing, students' writing can become more coherent and effective. These findings provide support for the aforementioned hypothesis. Consequently, to avail themselves of the opportunity to enhance their writing skills, students should recognize and embrace the practice of peer assessment throughout the writing process.